Determination of Value of String Bean and Cucumber Plants Factors Using Small Plots and USLE Methods on Andepts Soil in Kwala Bekala Estate USU - Muhammad Eko Hardiyansyah; Sumono Sumono; Saipul Bahri Daulay (Universitas Sumatera Utara, 2014)
One way to overcome erosion is using vegetative methods, where its influence can be manifested by the C factor. The best C factors used in determining the amount of erosion is the value of C in the local area. This study was aimed to determine the value of string bean and cucumber crop factors on the Andepts soil during April to August 2013 using the method of small plots and USLE. Parameters used in determining the C factor were the amount of erosion, the allowable erosion rate, and the erosion hazard level. The results showed that the amount of erosion on land without a crop was 0,46 ton (ha.year)-1,on cucumber land was 0,41 ton (ha.year)-1, on string bean land was 0,31 ton (ha.year)-1. The amount of allowable erosion rate was 31 ton (ha.year)-1. While erosion hazard rate on land without a crop was 0,014; on cucumber land was 0,013 and on string bean land was 0,010 which include in low category. The value of string bean crop factor using rainfall research data for 4 months and 10 years data was 0,685 and 0,690 respectively. The value of cucumber crop factor using rainfall research data for 4 months and 10 years data was 0,902 and 0,911 respectively Keywords : Andepts, C factor, Erosion, Kwala Bekala USU.